2013
DOI: 10.1002/ejlt.201200348
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrogenation and antioxidants on the stability of soybean oil biodiesels

Abstract: This study examined the influence of hydrogenation and antioxidant activity of natural products derived from Mangifera indica on soybean biodiesel stability. Biodiesels were prepared with refined, semi‐refined, and partially hydrogenated soybean oil and the stability was evaluated in a Rancimat apparatus. The biodiesel from partially hydrogenated soybean oil showed greater stability (11.9 h), exceeding the standard limit established by the Brazilian National Petroleum Agency (6 h). Gallic acid, tannic acid, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…However, problems associated with the use of 1st generation biodiesel remain inter alia its low oxidative stability and low-temperature behaviour as well as its higher NO x emissions [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Partial hydrogenation reactions of polyunsaturated FAME of vegetable oils to yield their monounsaturated (C18:1) counterparts [15,16,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][122][123][124][125][126][127][128][129][130][131] without increasing the content of the saturated part, i.e. methyl stearate (MS, Scheme 1) are useful reactions for upgrading 1st generation biodiesel [15,…”
Section: Partial Hydrogenation Reactions Of Renewable Polyunsaturatedmentioning
confidence: 99%
See 2 more Smart Citations
“…However, problems associated with the use of 1st generation biodiesel remain inter alia its low oxidative stability and low-temperature behaviour as well as its higher NO x emissions [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Partial hydrogenation reactions of polyunsaturated FAME of vegetable oils to yield their monounsaturated (C18:1) counterparts [15,16,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][122][123][124][125][126][127][128][129][130][131] without increasing the content of the saturated part, i.e. methyl stearate (MS, Scheme 1) are useful reactions for upgrading 1st generation biodiesel [15,…”
Section: Partial Hydrogenation Reactions Of Renewable Polyunsaturatedmentioning
confidence: 99%
“…Sonmez et al [65] partially hydrogenated sunflower oil using heterogeneous Pd/Rhbased scrap automobile catalyst to obtain high yield in trans-C18:1, elaidic acid. Alexandrino et al [66] investigated the oxidative stability of soybean oil biodiesel and of partially hydrogenated soybean oil biodiesel obtained with heterogeneous Ni-based hydrogenation catalysts and showed that the partially hydrogenated biodiesel possesses a higher oxidative stability which makes it better suited to commercialization. Su et al [67] used heterogeneous copper oxide bi-functional catalysts supported on alkaline earth metal oxides to catalyze both the transesterification reaction of hempseed oil with methanol to yield methyl esters of hempseed oil and the partial hydrogenation reaction of the highly unsaturated methyl esters of hempseed oil to produce their C18:1 counterparts which are suitable as a biodiesel fuel.…”
Section: Partial Hydrogenation Reactions Of Renewable Polyunsaturatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodiesel from partially hydrogenated soybean oil showed greater stability (11.9 h). The gallic acid showed higher antioxidant ability than other products, increasing twofold the oxidative stability (20.8 h) . Interaction of palm biodiesel with different polymer materials has been reviewed by Lutz et al .…”
Section: Stability and Biodegradation Of Biodieselmentioning
confidence: 99%
“…The most widely investigated methods are transesterification [7][8][9][10], catalytic cracking [11][12][13], and hydrodeoxygenation [14][15][16][17]. Transesterification of vegetable oil with lower alcohols, which yield fatty acid methyl esters (FAMEs), is performed under mild conditions and can be considered as a mature technology.…”
Section: Introductionmentioning
confidence: 99%